2010
DOI: 10.1073/pnas.1015691107
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-132 regulates dendritic growth and arborization of newborn neurons in the adult hippocampus

Abstract: Newborn neurons in the dentate gyrus of the adult hippocampus rely upon cAMP response element binding protein (CREB) signaling for their differentiation into mature granule cells and their integration into the dentate network. Among its many targets, the transcription factor CREB activates expression of a gene locus that produces two microRNAs, miR-132 and miR-212. In cultured cortical and hippocampal neurons, miR-132 functions downstream from CREB to mediate activity-dependent dendritic growth and spine forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
320
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 384 publications
(331 citation statements)
references
References 35 publications
9
320
1
1
Order By: Relevance
“…The knockout of Dicer specifically in postmitotic postnatal motor neurons in mice induces locomotor dysfuction due to the presence of a reduced number of motor neurons (30), indicating that a subset of miRNAs is essential for long-term survival of spinal motor neurons. Among the TDP-43-regulated miRNAs identified in this study, miR-132-3p is highly enriched in neurons and promotes neuronal outgrowth in vitro and in vivo by reducing the levels of the GTPase-activating protein, p250GAP (26,27). In this study, we demonstrated that the attenuation of neuronal outgrowth induced by TDP-43 depletion in differentiated Neruo2a cells can be attributed, at least in part, to the reduced expression of miR-132-3p and miR-132-5p induced by the loss of nuclear TDP-43 function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The knockout of Dicer specifically in postmitotic postnatal motor neurons in mice induces locomotor dysfuction due to the presence of a reduced number of motor neurons (30), indicating that a subset of miRNAs is essential for long-term survival of spinal motor neurons. Among the TDP-43-regulated miRNAs identified in this study, miR-132-3p is highly enriched in neurons and promotes neuronal outgrowth in vitro and in vivo by reducing the levels of the GTPase-activating protein, p250GAP (26,27). In this study, we demonstrated that the attenuation of neuronal outgrowth induced by TDP-43 depletion in differentiated Neruo2a cells can be attributed, at least in part, to the reduced expression of miR-132-3p and miR-132-5p induced by the loss of nuclear TDP-43 function.…”
Section: Discussionmentioning
confidence: 99%
“…S23 A-D). Considering that miR-132-3p is known to promote neuronal outgrowth in vitro and in vivo (26,27), we examined whether cotransfection of miRNAs could rescue the inhibited neurite outgrowth induced by TDP-43 depletion (Fig. 5 C-E).…”
Section: Tdp-43mentioning
confidence: 99%
“…Moreover, microRNAs achieve spatial specificity of gene expression in that they can regulate mRNA translation locally in the synaptodendritic compartment in an activity-dependent manner (Schratt, 2009b). As an example, miR-132 is critical for hippocampal spine formation and the inflammatory response (Shaked et al, 2009;Magill et al, 2010). miR-132 is thought to function together with FMRP to regulate translation in dendrites.…”
Section: Micrornas In Epigenetic Remodelingmentioning
confidence: 99%
“…cluding miR-132 and miR-134 target transcripts encoding proteins crucial to growth and remodeling of dendrites, thereby regulating synaptic strength and plasticity (19)(20)(21). MicroRNAs miR-9 and miR-124 target mRNAs involved in neurogenesis and integration of newborn neurons into the circuitry of the mature brain (22,23).…”
Section: Manipulating Micrornas In Murine Models: Targeting the Multimentioning
confidence: 99%